PEMANFAATAN ALAT SERPIH DI CERUK LAYAH KECAMATAN SAMPUNG, KABUPATEN PONOROGO, JAWA TIMUR (BERDASARKAN KAJIAN MIKROSKOPIS JEJAK PAKAI DENGAN PERBESARAN RENDAH) - katrynada jauharatna; Anggraeni . (JURNAL PANALUNGTIK, 2019)
Ceruk Layah is a site that located in Sampung Karst Region, Ponorogo, East Java. Based on the result of excavation conducted by Balai Arkeologi Yogyakarta in the ear of 2000-2002, the finds were dominated by stone artefacts and pottery fragments. Techno-economy study and stone artefacts classification had been done macroscopically. Further analysis is needed to ascertain whether stone tools in Ceruk Layah had been utilized by its occupants. There are three questions, concerning the variation of microware of the flake tools, the utilization of the flake tools, and the resistance of the worked materials on flake tools. This study applies macroscopic and microscopic analysis. Macroscopic analysis aims to determine the dimension, material, distribution, and location of microware of the flake tools. While microscopic analysis aims to identify the microware of flake tools by using low magnification (50 X), and to measure the depth and length of the fracture of the flake tools. The objective of the measurements of the fracture is to distinguish the fracture caused by flaking and utilization of the flake tools. The results of analysis shows that the sixteen pieces of flake tools in the Ceruk Layah carries three microwares which were dominated by fracture, while striation and polish were rarely found. In addition, each flake tool carries fracture that varies on the length and depth. The flake tools of Ceruk Layah might have been used for cutting, whittling, sawing, scraping, and boring. The resistance of the worked material consists of soft resistance, moderate resistance, and hard resistance.